Pengaruh Personal Branding Terhadap Brand Equity Produk Deodorant Jennskin Pada Akun TikTok @jennifer.coppen - Naflah; Herma Retno Prabayanti (The Commercium, 2025)
Abstract Personal Branding is one of the effective strategies to build a reputation for someone who is building a brand. This study aims to measure the level of significance of the variable elements, namely Jennifer Coppen's personal branding on her personal Tiktok account, towards the brand equity of Jennskin deodorant products. This study uses a quantitative approach. The population in this study were followers of the TikTok account @jennifer.coppen. The sampling technique in this study used the incidental sampling technique. The total respondents in this study were 400 respondents. Data analysis in this study used simple linear regression analysis with hypothesis testing using the t-test. The results of this study show that personal branding has a positive and significant effect on brand equity of 77.6%. While the remaining 22.4% is the coefficient value from other variables that were not tested in this study. The most dominant indicator of Jennifer Coppen's personal branding variable is the standard indicator, while in the brand equity variable the most dominant indicator is the brand loyalty indicator.